CRITICAL DISCOURSE STUDIES IN THE CONTEXT OF THE ARMENIAN CAUSE - Margaryan, Anahit (Armenian Folia Anglistika, 2025)
In this research, we aim to shape the understanding of Critical Discourse Studies (CDS) and its relation to the Armenian Cause. By examining the interdisciplinary approaches of CDS, we explore how language, power, and societal structures act within the context of the Armenian Genocide and the Nagorno-Karabakh conflict. This study identifies key discourse units such as statehood, genocide, ethnic cleansing, and us vs. them, and emphasizes the importance of international recognition and engagement in conflict resolution. Our research highlights the significance of legal frameworks, psychological healing, and socio-cultural structures in achieving sustainable peace and stability, thereby contributing to the broader discourse on social equality and justice. Through this analysis, we aim to enhance the academic and practical understanding of CDS and its application to complex historical and contemporary conflicts, the Armenian Cause.